2001
DOI: 10.1097/00000637-200103000-00019
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Skin Paddle Survival by Application of Vascular Endothelial Growth Factor in a Rat TRAM Flap Model

Abstract: The effect of vascular endothelial growth factor (VEGF) on skin flap survival and its ability to induce a pharmacological delay by promoting angiogenesis in a flap was studied in a rat transverse rectus abdominis musculocutaneous flap, using a 3 x 8-cm skin paddle with the inferior epigastric vessels as its main vascular supply. Forty-three Sprague-Dawley rats were divided into four groups. In group 1, VEGF was injected into the femoral vein after the flap was elevated. In group 2, VEGF was injected intra-arte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
61
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(64 citation statements)
references
References 35 publications
2
61
0
1
Order By: Relevance
“…In that study, the skin flap was 11×3 cm in size, and the average ratio of the viable surface area to the total flap area in the control group was 59%. The average ratio of viable surface area to total flap area was found to be highest in a study investigating the effects of the subdermal use of vascular endothelial growth factor (VEGF) on flap viability (27). The effect of VEGF on skin flap survival was studied in a rat transverse rectus abdominis musculocutaneous flap using a 3×8 cm skin paddle with the inferior epigastric vessels.…”
Section: Discussionmentioning
confidence: 99%
“…In that study, the skin flap was 11×3 cm in size, and the average ratio of the viable surface area to the total flap area in the control group was 59%. The average ratio of viable surface area to total flap area was found to be highest in a study investigating the effects of the subdermal use of vascular endothelial growth factor (VEGF) on flap viability (27). The effect of VEGF on skin flap survival was studied in a rat transverse rectus abdominis musculocutaneous flap using a 3×8 cm skin paddle with the inferior epigastric vessels.…”
Section: Discussionmentioning
confidence: 99%
“…Use of growth factors for the pharmacological delay for improvement of skin flap survival has been reported. 18 However, the application of the pharmacologi- cal delay with growth factors could be limited by their short half-life. ADSCs were first reported for improving neovascularization in the ischemic hind limb and ischemic myocardium in the animal model in 2001.…”
Section: Discussionmentioning
confidence: 99%
“…It was speculated that angiogenesis plays an important role in VEGF-165 protein therapy in augmentation of skin flap viability (36,37). However, other investigators reported that local subcutaneous or subdermal injection of VEGF-165 protein into rat skin flaps or musculocutaneous flaps at the time of surgery was also effective in augmenting skin viability (16,19,26,33,47,48). In addition, we demonstrated that intra-arterial infusion of VEGF-165 induced potent relaxation in isolated perfused pig skin flaps (2) and that acute local subcutaneous injection of VEGF-165 increased skin blood flow and viability in rat dorsal skin flaps (16).…”
mentioning
confidence: 99%